Synthesis of triazole-fused tetracyclic glycosides in aqueous medium: application of nanodomain cubic cuprous oxide as reusable catalyst in one-pot domino Sonogashira-cyclization. Issue 25 (17th June 2015) - Chatterjee, Nivedita; Pal, Rammyani; Sarkar, Swarbhanu; Sen, Asish Kumar
Graphical abstract: Abstract: An environmentally benign one-pot procedure has been developed for the syntheses of triazole-fused tetracyclic glycosides in aqueous medium. The two step one-pot synthesis involves Sonogashira reaction between azido-alkynes and aryl halides followed by intramolecular 1, 3-dipolar cyclization using cubic cuprous oxide nanoparticles as reusable catalyst, under aerobic condition. The method excludes the use of any surfactants or additional ligands as stabilizing agents. The catalyst could be used up to three recycles without any loss of catalytic activity. The method has a broad perspective for the synthesis of medium size ring systems.